Phase 2a, open-label, dose-escalating, multi-center pharmacokinetic study of favipiravir (T-705) in combination with oseltamivir in patients with severe influenza - Wang, Y; Zhong, W; Salam, A; Tarning, J; Zhan, Q; Huang, J-A; Weng, H; Bai, C; Ren, Y; Yamada, K; Wang, D; Guo, Q; et al. (Elsevier, 2020)
Background The pharmacokinetics and appropriate dose regimens of favipiravir are unknown in hospitalized influenza patients; such data are also needed to determine dosage selection for favipiravir trials in COVID-19.